2009
DOI: 10.1136/bmj.b4432
|View full text |Cite
|
Sign up to set email alerts
|

Is haemoglobin A1c a step forward for diagnosing diabetes?

Abstract: Eric Kilpatrick, Zachary Bloomgarden, and Paul Zimmet question proposals to diagnose diabetes by raised glycated haemoglobin concentration rather than glucose testing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 15 publications
1
84
0
2
Order By: Relevance
“…Therefore, provided that there is adequate screening for haemoglobinopathies and an appropriate method is used, accurate measurement of HbA 1c should be possible in people who are heterozygous for haemoglobinopathies. However, there is concern about the confusion created by the differences between instruments, with some analysers identifying certain variants but not others, and then other analysers picking up (or missing) a different range of variants [36].…”
Section: Measurement Of Hba 1cmentioning
confidence: 99%
“…Therefore, provided that there is adequate screening for haemoglobinopathies and an appropriate method is used, accurate measurement of HbA 1c should be possible in people who are heterozygous for haemoglobinopathies. However, there is concern about the confusion created by the differences between instruments, with some analysers identifying certain variants but not others, and then other analysers picking up (or missing) a different range of variants [36].…”
Section: Measurement Of Hba 1cmentioning
confidence: 99%
“…HbA1c testing can be performed at any time of the day and does not require any special pre-test preparation by the patient (for example, overnight fasting or glucose loading). 17,18 While the use of HbA1c for long-term glycaemic control is well accepted, there remains significant controversy on its use as a diagnostic tool, and many studies show significant discordance between fasting glucose and HbA1c tests.…”
Section: Hba1c and Diabetes Diagnosismentioning
confidence: 99%
“…Diabetic patients have a greater risk of developing a number of major health problems [11]. The incidence of diabetes is sharply increasing worldwide with many long-term macro-and micro-vascular complications [12,13]. The International Diabetes Federation reported that total number of diabetic subjects in India is 41 million in 2006 and that this would increase to 70 million by the year 2025 [14].…”
Section: Discussionmentioning
confidence: 99%